EFFETS DU CHANGEMENT CLIMATIQUE SUR LA DÉGRADATION DU PERGÉLISOL DANS LE N-O DE L’ITALIE : RÉSULTATS PRÉLIMINAIRES - FRATIANNI, SIMONA; COLOMBO, NICOLA; ACQUAOTTA, FIORELLA; GARZENA, DIEGO; GODONE, DANILO FRANCESCO; FREPPAZ, Michele; GIARDINO, Marco; Giaccone, E. (Michel Erpicum, 2015)
– Climate change effects on permafrost degradation in NW Italy. The aim of this work is to explain the first results obtained on climate change effects in periglacial environment of the Col d'Olen, in NW Italian Alps. Here, climate data analysis of high altitude meteorological stations and ground surface temperature survey of a rock glacier, a reliable permafrost indicator, are being conducted.